2020
DOI: 10.1109/jstars.2020.2988428
|View full text |Cite
|
Sign up to set email alerts
|

On Leaf BRDF Estimates and Their Fit to Microfacet Models

Abstract: Remote sensing provides high accuracy/precision for quantifying forest biophysical parameters needed for ecological management. Although the significant impact of bidirectional scattering distribution functions (BSDFs) on remote sensing of vegetation is well known, current forest metrics derived from sensor data seldom take leaf BSDF into account, and despite the importance of BSDF effects, leaf directional scattering measurements are almost nonexistent. Previous studies have been limited in the spectral cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The BRF data used in this segment of our analysis was measured in our laboratory using a hyperspectral goniometer, the Goniometer of the Rochester Institute of Technology‐Two (GRIT‐T) (Harms et al., 2017) covering a range of moisture content from dry to fully saturated (Eon & Bachmann, 2021a, 2021b). The GRIT‐T is a sophisticated goniometric system designed for use in field and laboratory settings and has seen widespread application in previous research (Bachmann, Eon, Ambeau, et al., 2018; G. Badura et al., 2019; G. Badura & Bachmann, 2019; G. P. Badura et al., 2019; Eon et al., 2018, 2020; Eon & Bachmann, 2021b; Roth et al., 2020, 2021; Shiltz & Bachmann, 2023). Users can create custom scan patterns to manage the system's arm, head, and carriage.…”
Section: Experimental Design and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BRF data used in this segment of our analysis was measured in our laboratory using a hyperspectral goniometer, the Goniometer of the Rochester Institute of Technology‐Two (GRIT‐T) (Harms et al., 2017) covering a range of moisture content from dry to fully saturated (Eon & Bachmann, 2021a, 2021b). The GRIT‐T is a sophisticated goniometric system designed for use in field and laboratory settings and has seen widespread application in previous research (Bachmann, Eon, Ambeau, et al., 2018; G. Badura et al., 2019; G. Badura & Bachmann, 2019; G. P. Badura et al., 2019; Eon et al., 2018, 2020; Eon & Bachmann, 2021b; Roth et al., 2020, 2021; Shiltz & Bachmann, 2023). Users can create custom scan patterns to manage the system's arm, head, and carriage.…”
Section: Experimental Design and Resultsmentioning
confidence: 99%
“…Badura et al, 2019;G. Badura & Bachmann, 2019; G. P. Badura et al, 2019;Eon et al, 2018Eon et al, , 2020Eon & Bachmann, 2021b;Roth et al, 2020Roth et al, , 2021Shiltz & Bachmann, 2023). Users can create custom scan patterns to manage the system's arm, head, and carriage.…”
Section: Smc Retrieval Using Laboratory Datamentioning
confidence: 99%
“…The surface reflectance of different vegetation is anisotropic due to its structural distribution. For example, BRDF distribution tests on wheat leaves [8], sorghum [9], maple leaves, and other leaves [10] can be found that different vegetation has different BRDF characteristic models. Therefore, based on the sensitivity of multi-angle BRDF data observation to vegetation structure, BRDF data can improve the accuracy of vegetation classification to 91% [11], which can improve the assessment of the ecological environment in different regions.…”
Section: Introductionmentioning
confidence: 99%